Applying the Racial Profiling Correspondence Test - Tanovich, David M. (2017)
In the landmark Canadian racial profiling case of R v Brown, an unanimous Ontario Court of Appeal firmly recognized that racial profiling is a reality that is “supported by significant social science research.”
Keywords: David Tanovich